2023
DOI: 10.1021/jacs.2c13732
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Responsive Double-Locked Photodynamic Molecular Beacon for Targeted Photodynamic Anticancer Therapy

Abstract: An advanced photodynamic molecular beacon (PMB) was designed and synthesized, in which a distyryl boron dipyrromethene (DSBDP)-based photosensitizer and a Black Hole Quencher 3 moiety were connected via two peptide segments containing the sequences PLGVR and GFLG, respectively, of a cyclic peptide. These two short peptide sequences are well-known substrates of matrix metalloproteinase-2 (MMP-2) and cathepsin B, respectively, both of which are overexpressed in a wide range of cancer cells either extracellularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…HCFU (72%) -TTPP (28%) -SPNs display less than 20% HCFU and TTPP release within 96 h under physiological pH conditions (pH 7.4) and in a slightly acidic medium (pH 6.5, Figure m, as well as Figure S19 in the Supporting Information). In contrast, a relatively faster HCFU and TTPP release is observed at pH 5.0, similar to the lysosomal environment . Nearly 85% of HCFU and 81% of TTPP could be effectively released from HCFU (72%) -TTPP (28%) -SPNs after incubation of 96 h (Figure m, as well as Figure S19 in the Supporting Information), indicating the breaking of the majority of H-bonding association, therefore reflecting a pH-responsive smart HCFU and TTPP release.…”
Section: Resultsmentioning
confidence: 89%
“…HCFU (72%) -TTPP (28%) -SPNs display less than 20% HCFU and TTPP release within 96 h under physiological pH conditions (pH 7.4) and in a slightly acidic medium (pH 6.5, Figure m, as well as Figure S19 in the Supporting Information). In contrast, a relatively faster HCFU and TTPP release is observed at pH 5.0, similar to the lysosomal environment . Nearly 85% of HCFU and 81% of TTPP could be effectively released from HCFU (72%) -TTPP (28%) -SPNs after incubation of 96 h (Figure m, as well as Figure S19 in the Supporting Information), indicating the breaking of the majority of H-bonding association, therefore reflecting a pH-responsive smart HCFU and TTPP release.…”
Section: Resultsmentioning
confidence: 89%
“…As such, the development of near-infrared photosensitizers or a switch to SDT is necessary. 115–119 Second, although aPDT alone is effective against Gram-positive bacteria, it is often inadequate against Gram-negative bacteria due to their unique outer membrane structure. 120 Consequently, the development of photosensitizers with destructive effects on the outer membrane is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, photothermal therapy (PTT) and photodynamic therapy (PDT) have attracted considerable attention as viable treatment strategies against bacterial infection. For example, Qiu et al constructed a photosensitive covalent organic framework (TAPP-BDP) as an antibacterial agent, which exhibited excellent antibacterial efficiency through synergistic photodynamic/photothermal/nanozymatic therapy . PTT uses photothermal agents (PTAs) that absorb specific wavelengths of light to convert light into thermal energy, causing bacterial apoptosis. PDT, on the other hand, employs photosensitizers (PSs) to sensitize oxygen and produces reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), hydroxyl radical ( • OH), hydrogen peroxide (H 2 O 2 ), and superoxide anion radical (O 2 – ), which are cytotoxic oxidizing agents and can react with proteins and DNA to cause bacterial cell damage. These therapies have the advantages of being noninvasive, highly efficient, and easy to operate and having minimal side effects. However, PTT or PDT alone requires higher temperatures or longer illumination times to completely kill bacteria, and prolonged illumination times will damage the adjacent healthy tissues, resulting in low treatment efficiency. Consequently, combined PDT/PTT therapy could provide an effective solution to these issues. Based on this theory, Guan et al reported a nanoscale COF (NCOF)-based PDT/PTT dual-modal therapeutic agent obtained via stepwise bonding defect functionalization and guest encapsulation processes.…”
Section: Introductionmentioning
confidence: 99%